PSYCHOLINGUISTIC ANALYSIS OF COMMUNICATION - Tkachenko, Nataliya (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article represents the outlook of modern methods of psycholinguistic analysis of the dialogue semantics, the semantic vector being the most prospective in modern discourse linguistics. The experimental methods in psycholinguistics are rather new, and our research is an attempt to apply them to the dialogue study and suggest some new methods. Psycholinguistic analysis reveals the numerous interdisciplinary links in interpreting the human speech behavior: with cognitive linguistics, pragmatic linguistics, sociolinguistics, cultural linguistics as psychic is expressed іn multiple ways. Linguistic methods of analysis comprise field and text investigation. The field analysis reflects the words organization and their links in human mentality. The descriptive and interpretation vectors of analysis include contextualization, conversational, conceptual and discourse analysis. The pragmatic vector of psycholinguistic analysis reveals the interlocutors’ attitude and influence. The sociolinguistic vector of analysis determines the reason of the psychic states of the interlocutors in communication situations. The cognitive vector of analysis reveals the interlocutors’ speech strategies. Experimental methods of semantic interaction, semantic differential, gradual scaling, introspective and intentional analysis can also be used for description and interpretation in dialogue semantics studies. The statistic methods include calculating the text size, sentences quantity, their medium length, words variety coefficient, the coefficients of nouns, verbs, embolia, aggressiveness and cohesion and the content analysis. ______________ References: • Andreychuk,N. I. (2010). Zhitteviy svit ludini v angliyskimu institutsiinomy diskursi epokhi Tudoriv [The human outlook in the English institutional discourse of Tudor period] Mova I kultura [Naukove vidannia]. 13 (II, 138): 75-82, https:// burago. com.ua/wp-content/ uploads/ 2018/03/138.pdf. • Druzhina, A. (2019) Psykholinvysychnyi pidkhid do analizu khudozhnyiogo tvoru (na materialy urivka z romanu M. L. Stedman “The Light Between Oceans”. [Psycholinguistic approach to the analysis of the abstract from the novel by M. L. Stedman “The Light Between Oceans”]. Lingvistichny nauki 28: 86-94, https://orcid.org/0000–0002–2679. • Kalischuk, D. M. (2007). Analis intentsiy movtsya yak peredumova adekvatnoi interpretatsii polituchnikh tekstiv [Analysis of the speaker’s intentions preceding the adequate interpretation of the political texts]. Philologicni studii: naukovii chasopis1/2: 247-252, https://evnuir.vnu. edu.ua/ bitstream/ 123456789/ 3936/ 3/political.pdf. • Kalmikova, L. O., Kalmikov, G. V., Lapshina, I. M., Kharchenko, N. V. (2017). Psikholohiia Movlennia i psykholinhvistyka: navchalniy posibnik, https://pedagogy.lnu.edu.ua/wp-content/uploads/2017/05/Kalmykova_Psykholohiia-movlennia-i-psykholinhvistyka.pdf. • Kapturova, V.V. (2013). Komunikativni strategii koristuvachiv sotsialnikh merezh ta mikroblogiv [The communicative strategies of the social networks and mikroblogs users]. Lingvistika ХХІ stolittia: novi doslidzhennia I perspectivy: 104-111, http://langcenter.kiev.ua/ Lingvistika%202013/ Kapturova_V.pdf. • Коzachenko,A. (2016). Psikholingvisitichny analis vnutrishnogo monologue geroya dramatichnogo tvoru (na osnovi drami Bertolda Brekhta “Zhittia Galileo”) [Psycholinguistic analysis of the inner monologue of the drama character (based on the Bertold Brekht drama “Life of Galileo”]. Mezhdunarodniy electronniy nauchniy zhurnal 2(12), www.pathofscience.org. • Kuranova,I. (2012) Osnovy psikholingvistiki [Psycholinguistics Fundamentals]. Textbook (Kyiv: Akademia), https://evnuir.vnu.edu.ua/bistream/123456789/ 18655/1/psyholingv.pdf • Lopatin,N. (1902). «Metod sposterezhennya v psikhologii.» [Observation method in psychology] Pitannya philosophii ta psichologii II (62), 1068. • Dіjk,Teun A. Van. (2022) «Dialogue and cognition.» Problems and Aims: 1-17, http://www.discourses.org/Old Articles/Dialogue%20Cognition.pdf • Pickering,Martin J. The Dance of dialogue, https://thepsychologist.bps.org.uk/volume-19/edition-12/dance-dialogue. • Potter, Edwards,D. (2012). Conversation Analysis and Psychology: 701-705, https://sites.tufts.edu/hilab/files/2017/09/Potter-Edwards-CA-and-Psychology-Handbook-of-CA-proof-2012.pdf. • Dictionary of Ukrainian Language, https://slovnyk.ua/index.php?swrd. • Psycholinguistics, https://en.wikipedia.org/wiki/Psycholinguistics.